ECM‐derived Scaffolds: Scaffolds Functionalized with Matrix from Induced Pluripotent Stem Cell Fibroblasts for Diabetic Wound Healing (Adv. Healthcare Mater. 16/2020). Issue 16 (19th August 2020) - Santarella, Francesco; Sridharan, Rukmani; Marinkovic, Milica; Do Amaral, Ronaldo Jose Farias Correa; Cavanagh, Brenton; Smith, Avi; Kashpur, Olga; Gerami‐Naini, Behzad; Garlick, Jonathan A.; O'Brien, Fergal J.; Kearney, Cathal J.
Abstract : Extracellular matrix (ECM)‐derived scaffolds show promise in a variety of tissue engineering applications. In article number 2000307, Cathal J. Kearney and co‐workers exploit ECM grown by cells differentiated from induced pluripotent stem cells for scaffold fabrication and examine their potential for diabetic wound healing. This ECM has previously been shown to be enriched in foetal‐like components, which can augment healing.